A Method of Investigating the Ageing Perception and Satisfaction towards Product Appearances - Majid, Ahmad Zuhairi Abdul; Jamalludin, Nurazlina (2017)
The purpose of this paper is to proposing a method investigating on product appearance perceived by the ageing consumers.It also examines the relationship between ageing perception towards product appearance in oder to better understand how they will respond to products as they grow older.